Testing the Limits of Sex Differences Using Variable Stress. (1st February 2021) - Johnson, Alyssa; Rainville, Jennifer R.; Rivero-Ballon, G. Nicole; Dhimitri, Katerina; Hodes, Georgia E.
Highlights: A composite stress susceptibility score unifies behavior across tests. Male and female mice are susceptible to variable stress 30 days later. Mice habituate to 56 days of variable stress for most tests. Behavioral tests correlate to a unified score and not each other in both sexes. Abstract: Depression is a chronic disease that affects nearly twice as many women as men, and symptoms can differ by sex. Preclinical models disproportionately use male subjects and test a single behavioral endpoint immediately at the cessation of stress. We conducted variable stress in male and female mice for 6, 28, and 56 days, and measured behavior with a battery chosen to match research domain criteria. To examine individual differences, we generated a composite z score to measure stress susceptibility across behavioral tests. We also tested behavior following a 30-day recovery period to evaluate the duration of the stress effects. Females, but not males, were susceptible to 6 days of variable stress when behavioral testing started 24 h later. If behavioral testing was conducted 30 days later both males and females expressed stress related behaviors. Males and females were stress susceptible to 28 days of variable stress and effects were long lasting. Both sexes habituated to 56 days of variable stress, but anxiety associated measures still showed persistence. Performance on specific behavioral tests was often different between individuals and between sexes, and not all stressed animals were susceptible to all tested behaviors. These studies confirm that behavioral sex differences are detected in response to variable stress, and reveal information about individual differences. Use of a test battery that measures varying endophenotypes can be combined into a single stress susceptibility score as a tool similar to the scales/inventories used for the study of depression in humans. We present these data with the goal of furthering the field's understanding sex differences and how they shape the biology of mood disorders.